Role of methamphetamine metabolism in the development of CNS tolerance to the drug - Alburges, Mario; Hanson, Glen; Gibb, James (Investigación Clínica, 2013)
We have previously observed that pretreatment with increasing doses of methamphetamine (METH) attenuates the effects of METH on the dopaminergic and serotonergic systems as compared with the ones observed in nonpretreated controls. In order to understand the mechanism of this tolerance, untreated rats (naive) and rats pretreated with METH (daily doses of 2.5, 5.0, 7.5 and 10 mg/kg, s.c., at 6h intervals with a 24h drug-free period between each dose) were challenged with the administration of 5 doses of METH (15 mg/kg, S.C., at 6h intervals). The metabolism of METH in brain, liver, and blood was studied by measuring the concentration of METH and its metabolites 2, 4, 6,8 and 10h after the last dose by gas chromatography/ mass spectrometry techniques. The forebrain concentrations of METH in the pretreated animals were significantly lower than those observed in the forebrain of naive animals. Liver concentrations of METH in the pretreated animals were not significantly modified as compared to the ones of naive animals, but in the liver amphetamine and the p-hydroxylated metabolites, p-hydroxyamphetamine (p-OH-AMP) and p-hydroxymethamphetamine (p-OH-METH), were significantly greater than those observed in the naive group. Blood levels of METH, AMP and their p-hydroxylated metabolites were also greater in the pretreated animals. The involvement of an altered distribution of methamphetamine in the CNS and the development of tolerance is discussed.